Using Video to Increase Gender Bias Literacy Toward Women in Science. (June 2017) - Pietri, Evava S.; Moss-Racusin, Corinne A.; Dovidio, John F.; Guha, Dipika; Roussos, Gina; Brescoll, Victoria L.; Handelsman, Jo
Despite evidence that gender biases contribute to the persistent underrepresentation of women in science, technology, engineering, and mathematics, interventions that enhance gender bias literacy about these fields remain rare. The current research tested the effectiveness of two theoretically grounded sets of videos at increasing gender bias literacy as characterized by (a) awareness of bias, (b) knowledge of gender inequity, (c) feelings of efficacy at being able to notice bias, and (d) recognition and confrontation of bias across situations. The narrative videos utilized entertaining stories to illustrate gender bias, while the expert interview videos discussed the same bias during an interview with a psychology professor. The narrative videos increased participants' immersion in the story and identification with characters, whereas the expert interviews promoted logical thinking and perceptions of being knowledgeable about gender bias facts. Compared with control videos, the narrative and expert interview videos increased awareness of bias (Experiments 1 and 2) and influenced knowledge of gender inequity, self-efficacy beliefs, and the recognition of bias in everyday situations (Experiment 2). However, only the expert interview videos affected participants' intentions to confront unfair treatment. Additional online materials for this article are available to PWQ subscribers on PWQ's website at http://pwq.sagepub.com/supplemental